Between the Tongkonan building and the Marampaâ€™ Church: The strategy of â€œadaptive spaceâ€ for the Torajan migrant community in Jayapura City - Frisca Novia Adventin; Fred Keith Hutubessy (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2021)
This paper examines the strategies of Torajan migrants that helped them to adapt to Jayapura City. This study was inspired by Edward Brunner and Suparlan to understand the concept of the dominant culture. This study uses qualitative research methods, collected by observations, interviews, documentation techniques, and through some of the literature on the migration of the Toraja people. The informants in this study is people who had come in the early days to Jayapura City. They were also members of the Toraja Family Association. These studies found out that the migrants tended to follow the dominant culture, dominated the dominant culture, and created the rules of the game for all communities to follow. They also have identity symbols, such as the Tongkonan building and the Marampaâ€™ Church in Jayapura City. Hypothetically, these symbols show that they are able to adapt to Jayapura City. This study found that the Torajan migrant community in Jayapura took advantage of a strategy called â€œadaptive space.â€ This strategy is carried out through cultural redefinition and by identifying similarities with the dominant culture. They also provide for the common needs in the dominant culture and constructing external relations to adapt in Jayapura City.